New Literacies of Online Research and Comprehension - Leu, Donald J.; Kiili, Carita; Forzani, Elena; Zawilinski, Lisa; O'Byrne, W. Ian; McVerry, J. Greg (The Encyclopedia of Applied Linguistics, 2021)
This entry explores the question of how to conceptualize literacy as a deictic concept, one that continually changes as new technologies for literacy and learning emerge. It suggests a dual-level conceptualization of theory: a New Literacies theory as an overarching theory that encompasses perspectives and findings from the many studies of literacy, which are referred to as new literacies theories, using lower case. It then focuses special attention on an important lower-case theory, the new literacies of online research and comprehension. This new literacies theory frames online reading as a process of problem-based inquiry involving the new skills, strategies, dispositions, and social practices that take place as we use the Internet to solve problems and answer questions. Current understanding of online reading to learn from a New Literacies perspective is informed by recent research using assessments that measure students' ability to conduct online research in science and comprehend what they read in a virtual online world. Findings suggest that online reading requires different skills than reading paper materials; that differences across modes of reading are important for school learning; and that the Internet is best conceived as a literacy issue rather than a technology issue.
Keywords: Literacy; Literacy Practices Online; New Literacies; Online Reading; Teaching Reading; dept.cur

The new literacies of online reading comprehension: expanding the literacy and learning curriculum - Leu, Donald J.; McVerry, J. Gregory; O'Byrne, W. Ian; Kiili, Carita; Zawilinski, Lisa; Everett-Cacopardo, Heidi; Kennedy, Clint; Forzani, Elena (Journal of Adolescent & Adult Literacy, 2011)
Keywords: dept.cur